Analysis of Transients in a 4-Level Flying Capacitor Converter: Time Domain Approach. Part 1: Large Normalised Voltage Command - Reznikov Boris; Ruderman Alex; Galanina Valentina (Power Electronics and Drives, 2020)
A 4-level flying capacitor converter (FCC) operation is considered on a base of discrete state-space model. A transition matrix is obtained for a pulse width modulation (PWM) period for large normalised voltage command values [1/3, 1). The transition matrix elements are expanded into power series by small parameters. The matrix eigenvalues are presented in the form of power series as well. Six separate transients are constructed for six possible initial FCC states on a PWM period. Inductor current and capacitors’ voltage transients are found for the voltage source power-up as the arithmetic average of the six separate transients. Finally, the discrete solutions are replaced by equivalent continuous ones. Simple and accurate formulas for inductor current and capacitors’ voltage transients demonstrate good agreement with simulation results.